The state of green open access in Canadian universities - Riddle, Poppy; Simard, Marc-André; Gone, Pallavi; Li, Vinson; Mongeon, Philippe (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie, 2023)
This study investigates the use of institutional repositories for self-archiving peer-reviewed work in the U15 (an association of fifteen Canadian research-intensive universities). It relates usage with university open access (OA) policy types and publisher policy embargoes. We show that of all articles found in OpenAlex attributed to U15 researchers, 45.1 to 56.6% are available as Gold or Green OA, yet only 0.5 to 10.7% (mean 4.2%) of these can be found on their respective U15 IRs. Our investigation shows a lack of OA policies from most institutions, journal policies with embargoes exceeding 12 months, and incomplete policy information.